Democratization in Spain and the role of the EC/ EU - Korkmazarslan, Serkan (My University, 2007)
İSPANYA’DA DEMOKRATİKLEŞME VE AT/ AB’NİN ROLÜ Bu çalışma İspanya’daki demokratikleşmeyi özellikle Avrupa Topluluğu/ Avrupa Birliği’ne üyelik sürecine ilişkin olarak incelemektedir. Tezin temel argümanı, aslında ülkelerin ulusal sınırları içerisinde gerçekleşen ve bu nedenle ulusal aktör ve faktörlerin baskın olduğu demokratikleşme süreçlerinin önemli bir uluslararası boyutunun da olduğudur. Bu kapsamda, İspanya’daki demokratikleşme sürecine de Avrupa Topluluğu/ Avrupa Birliği’nin çok önemli bir katkıda bulunduğunu savunmaktadır. DEMOCRATIZATION IN SPAIN AND THE ROLE OF THE EC/ EU This thesis examines the democratization in Spain particularly within the context of its accession to the European Community/ European Union. It argues that democratization, which actually occurs within domestic boundaries, and therefore notwithstanding the dominant role of domestic actors and factors, has also an important international dimension. In other words, it argues that the EC/ EU and the European integration process have made a significant contribution to the democratic transformation of Spain.
Keywords: Demokrasi